2016
DOI: 10.1186/s40064-016-3764-2
|View full text |Cite
|
Sign up to set email alerts
|

Chinese insurance agents in “bad barrels”: a multilevel analysis of the relationship between ethical leadership, ethical climate and business ethical sensitivity

Abstract: BackgroundThe moral hazards and poor public image of the insurance industry, arising from insurance agents’ unethical behavior, affect both the normal operation of an insurance company and decrease applicants’ confidence in the company. Contrarily, these scandals may demonstrate that the organizations were “bad barrels” in which insurance agents’ unethical decisions were supported or encouraged by the organization’s leadership or climate.ObjectiveThe present study brings two organization-level factors (ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 72 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…ethical climate, job satisfaction, organizational commitment, and organizational citizenship behaviors). 40,41 Therefore, the role of workplace bullying on the moral distress–burnout relationship is expected in our hypothesis. Indeed, nurses who perceive moral distress and feel to be victim of bullying might report burnout.…”
Section: Introductionmentioning
confidence: 65%
“…ethical climate, job satisfaction, organizational commitment, and organizational citizenship behaviors). 40,41 Therefore, the role of workplace bullying on the moral distress–burnout relationship is expected in our hypothesis. Indeed, nurses who perceive moral distress and feel to be victim of bullying might report burnout.…”
Section: Introductionmentioning
confidence: 65%
“…First, a negative relationship exists between ethical leadership and workplace deviance (Gok et al , 2017). Second, a positive relationship exists between ethical leadership and ethical climate (Demirtas and Akdogan, 2015; Lu and Lin, 2014; Zhang and Zhang, 2016). Third, a negative relationship exists between ethical climate and deviant behavior (Mayer et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Demirtas and Akdogan (2015) found a mediating role of ethical climate in the relationship between ethical leadership and individual’s outcomes. Recently, Zhang and Zhang (2016) found that organizational ethical climate fully mediates the relationship between ethical leadership and business ethical sensitivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relational leadership is not only directed towards the interests of the organization, but also actively empowers employees, giving them more freedom and flexibility at work. When employees face ethical dilemmas, they may not strictly abide by the relevant code of conduct, but rather violate the rules for the benefit of the organization [32]. Based on the arguments presented above, this study proposes the following assumptions:…”
Section: Theory and Hypothesismentioning
confidence: 99%